2020
DOI: 10.1007/s00268-020-05575-2
|View full text |Cite
|
Sign up to set email alerts
|

Hazardous Postoperative Outcomes of Unexpected COVID‐19 Infected Patients: A Call for Global Consideration of Sampling all Asymptomatic Patients Before Surgical Treatment

Abstract: Background In December 2019, a novel coronavirus was identified as the cause of many pneumonia cases in China and eventually declared as a pandemic as the virus spread globally. Few reports were published on the outcome of surgical procedures in diagnosed COVID-19 patients and even fewer on the surgical outcomes of asymptomatic undiagnosed COVID-19 surgical patients. We aimed to review all published data regarding surgical outcomes of preoperatively asymptomatic untested coronavirus disease 2019 (COVID-19) pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
95
2
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(106 citation statements)
references
References 21 publications
4
95
2
5
Order By: Relevance
“…Additionally, the rate of cesarean sections is among the highest in the world and questions remain regarding the increased risk of postoperative morbidity and mortality for patients with COVID-19 undergoing surgery. 8 Our findings identified diabetes, cardiovascular disease, and obesity as significant conditions associated with mortality in the obstetric population, similar to the general population ( to 14.6% of all fatal cases, while the remaining 21,4% received non-invasive ventilation only. Failure to adequately report these variables in the surveillance system cannot be ruled out due to its retrospective nature.…”
Section: Introductionsupporting
confidence: 74%
“…Additionally, the rate of cesarean sections is among the highest in the world and questions remain regarding the increased risk of postoperative morbidity and mortality for patients with COVID-19 undergoing surgery. 8 Our findings identified diabetes, cardiovascular disease, and obesity as significant conditions associated with mortality in the obstetric population, similar to the general population ( to 14.6% of all fatal cases, while the remaining 21,4% received non-invasive ventilation only. Failure to adequately report these variables in the surveillance system cannot be ruled out due to its retrospective nature.…”
Section: Introductionsupporting
confidence: 74%
“…Patients with COVID-19 disease who undergo surgery suffer a complicated postoperative course [ 5 , 6 ]. Studies have shown that up to 51.2% of these patients had pulmonary complications and among patients who had pulmonary complications after surgery 30-day mortality rate was 38% [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Equally, the Indian Journal of Surgery is bringing out the views of surgeons in its publications Indian Journal of Surgery and has already published special consent form for COVID-19 patients [38]. Most guidelines agree that elective surgery on positive COVID-19 patients should be deferred, until they have been asymptomatic for 72 h and have at least 2 negative COVID-19 tests separated by at least 24 h. Similarly, they also recommend preoperative COVID-19 testing for each patient because if an asymptomatic carrier undergoes surgery or if a perio p e r a t i v e p a ti e n t c o n t a c t s C O V I D -1 9 ; r e l a t i v e immunocompromise after major surgical intervention may worsens the prognosis and overall outcome with unacceptable mortality rate and a high rate of severe complications [14,39]. It is wise and safe to follow the current axiom: "most effective way to prevent viral exposure is to avoid performing nonessential surgical procedures" as this limits the exposure to patients and clinicians, conserves PPEs, and preserves health system capacity [24].…”
mentioning
confidence: 99%